Human De Novo Papillary Renal‐Cell Carcinomas in a Kidney Graft: Evidence of Recipient Origin With Adenoma‐Carcinoma Sequence. Issue 4 (20th February 2013) - Verine, J.; Varna, M.; Ratajczak, P.; El‐Bouchtaoui, M.; Leboeuf, C.; Plassa, L.‐F.; Soliman, H.; Sandid, W.; Abboud, I.; Bousquet, G.; Verneuil, L.; Peraldi, M.‐N.; et al.
Abstract : Papillary renal‐cell carcinoma (pRCC) is unusual for its occurrence in kidneys with chronic dysfunction, for its frequent multifocality and for its common association with papillary adenoma, a benign renal lesion morphologically indistinguishable from pRCC. Concomitant development of papillary adenoma and pRCC in five transplanted kidneys, where donor and recipient characteristics are well established, provided a unique opportunity for molecular studies of de novo pRCC carcinogenesis. We aimed to study this tumor type to determine whether or not the different papillary tumors have the same origin, and whether or not papillary adenomas are precursor lesions of pRCC. We performed XY‐FISH in sex‐mismatched kidney transplants, and polymorphic microsatellite DNA and high‐resolution melting of mitochondrial DNA analyzes in all five patients on laser‐microdissected tumor cells, then compared these molecular profiles to donor and recipient profiles. This study (i) identified the recipient origin of de novo papillary adenomas and pRCCs in a kidney transplant, (ii) demonstrated an identical origin for precursor cells of papillary adenomas and pRCCs and (iii) showed additional genetic alterations in pRCCs compared to papillary adenomas. This molecular approach of papillary tumors developed in transplanted kidney identified successive steps in carcinogenesis of human de novo papillary renal‐cell carcinoma. Abstract : Using the unique opportunity provided by the concomitant development of papillary adenoma and papillary renal‐cell carcinoma in kidney transplants, this study demonstrates that papillary renal‐cell carcinoma may arise from recipient cells according to a multistep tumorigenesis process.